Physical Activity, Lipid Profile and Other Cardiovascular Risk Factors in the Africans: Results of the Vitaraa Study (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: physical activity; lipid profile; cardiovascular risk factors; africans